2D and 3D Ruthenium Nanoparticle Covalent Assemblies for Phenyl Acetylene Hydrogenation. Issue 43 (5th November 2020) - Min, Yuanyuan; Leng, Faqiang; Machado, Bruno F.; Lecante, Pierre; Roblin, Pierre; Martinez, Hervé; Theussl, Thomas; Casu, Alberto; Falqui, Andrea; Barcenilla, María; Coco, Silverio; Martínez, Beatriz María Illescas; et al.
Abstract : The bottom‐up covalent assembly of metallic nanoparticles (NP) represents one of the innovative tools in nanotechnology to build functional heterostructures, with the resulting assemblies showing superior collective properties over the individual NP for a broad range of applications. The ability to control the dimensionality of the assembly is one of the major challenges in designing and understanding these advanced materials. Here, two new organic linkers were used as building blocks in order to guide the organization of Ru NP into two‐ or three‐dimensional covalent assemblies. The use of a hexa‐adduct functionalized C60 leads to the formation of 3D networks of 2.2 nm Ru NP presenting an interparticle distance of 3.0 nm, and the use of a planar carboxylic acid triphenylene derivative allows the synthesis of 2D networks of 1.9 nm Ru NP with an interparticle distance of 3.1 nm. The Ru NP networks were found to be active catalysts for the selective hydrogenation of phenylacetylene, reaching good selectivity toward styrene. Overall, we demonstrated that catalyst performances are significantly affected by the dimensionality (2D vs. 3D) of the heterostructures, which can be rationalize based on confinement effects. Abstract : Two new organic linkers were used as building blocks in order to guide the organization of Ru nanoparticles into two‐ or three‐dimensional covalent assemblies. The catalyst performances for phenyl acetylene hydrogenation are significantly impacted by the dimensionality of the produced assemblies, which can be rationalize based on electronic and confinement effects.